Employee involvement in Decision Making on Performance of SME’s in Kitale, Trans Nzoia County, Kenya - W. Chesoli, Dr. Joshua (IJRDO - Journal of Business Management, 2018)
This study examined the effect of employee involvement in decision making on performance of selected SMEs in Kitale. Data was sourced from one hundred and twenty nine (129) employees and twenty seven (27) owner/managers of the randomly selected SMEs, with the aid of questionnaire. The datagenerated were statistically analyzed using descriptiveinferential statistical tools. Results showed that’ on overall, employee participation in decision making had significantpositive impact on organizational performance in the SMEs, with (β = 0.597, t = 6.572, P<.01).The implication of this finding is that Kenyan SMEs should pay attention to human resource management practices which, they have hitherto, largely ignored, in the course of running their businesses. Increasing employee involvement in decision making will impact positively on their growth and potential for survival.